Efectividad de la enfermería especializada en quirófano en la prevención de eventos adversos: una revisión sistemática - Santos Zambrano, Jazmina María (2026)
Since 1970 in the United States, the certification of instrumentation nurse has been issued, so nursing is in constant evolution and training to provide care, and thus prevent adverse events in the operating room. Therefore, the objective of this research is to evaluate the effectiveness of the care provided by nurses specialized in operating room in the prevention of adverse events through a systematic review of the scientific literature published in the last five years. The methodology of this research was qualitative with a non - experimental design because the variables were not manipulated. Of the 100 records identified in databases such as Pubmed, Scielo, Elsevier, among others; 14 studies were analyzed, using the PRISMA method, and the main results coexisted that continuing education is the right way to provide care and address the consequences of adverse events, in addition to the fact that the updating of knowledge is advisable to perform it with innovative technology, thus obtaining as a conclusion that having trained personnel in the operating room, is beneficial for patient safety and to improve the performance of the service in general, because learning is daily, both professional and human.